Transforming the residential built environment: Land-use policies and the influence of the growth machine across the United States - Adua, Lazarus; Lobao, Linda (Social science research, 2024)
What effects do growth machine actors have on transformation of the built environment in terms of localities' enacted land-use policies and actual development? To the best of our knowledge, this study is among the first to answer this question for communities across the United States. We draw on the growth machine theory and speak to some of its proponents’ puzzling findings that policies designed to limit growth often facilitate it. Our analysis is grounded in the urban-quantitative tradition of large-sample studies of U.S. localities. We find that involvement of growth machine business actors in local government is related to transformation of the built environment as indicated by the issuance of new residential building permits. Intriguingly, involvement of local growth actors is also associated with greater use of land-use control policies, which, in turn, have positive rather than negative effects on issuance of new residential building permits. Thus, it seems growth machine actors support policies that outwardly appear to stymie growth, although they in practice do not. These findings suggest land-use policies are often designed with enough leeway for continued growth. Supporting such policies allows growth machine actors to publicly signal support for managed growth and environmental protection, although the reality on the ground remains business as usual.